(untitled) (Research, Society and Development, 2021)
Just a few years ago, within the context of economic globalization of the last 20th century and during the technological revolution, organizations and institutions, together with the concept of work itself, have logically reconfigured the profile of skills required of young people and workers, too. Society, progressively with the change, is requiring competent professionals in increasingly transversal fields, and we find ourselves faced with the need to possess high capacities for adaptation and updating. Versatile people are called for, capable not only in the closed circle of their work environment, but also with group work attitudes, adaptability, flexibility, among others. This intervention project arises from the need to provide young people with transversal job skills that are currently required in the professional market. The competences that acquire the most prominence in this intervention project are some such as teamwork and social skills, being essential competences to be developed by a pedagogue. The recipients of this project are recent graduates in pedagogy from the University of Murcia. It will take place at the Regional Employment and Training Service, as it is aimed at clarifying the professional future of young people, who are going through a critical situation in our country. Through a series of activities, these competences will be enhanced, in order to promote autonomy for the active search for employment. Thus, it is hoped to promote the fruitful search for employment of recently graduated pedagogues.